Democratic Frontiers Algorithms and Society (Taylor & Francis, 2022)
Democratic Frontiers: Algorithms and Society focuses on digital platforms' effects in societies with respect to key areas such as subjectivity and self-reflection, data and measurement for the common good, public health and accessible datasets, activism in social media and the import/export of AI technologies relative to regime type. Digital technologies develop at a much faster pace relative to our systems of governance which are supposed to embody democratic principles that are comparatively timeless, whether rooted in ancient Greek or Enlightenment ideas of freedom, autonomy and citizenship. Algorithms, computing millions of calculations per second, do not pause to reflect on their operations. Developments in the accumulation of vast private datasets that are used to train automated machine learning algorithms pose new challenges for upholding these values. Social media platforms, while the key driver of today's information disorder, also afford new opportunities for organized social activism. The US and China, presumably at opposite ends of an ideological spectrum, are the main exporters of AI technology to both free and totalitarian societies. These are some of the important topics covered by this volume that examines the democratic stakes for societies with the rapid expansion of these technologies. Scholars and students from many backgrounds as well as policy makers, journalists and the general reading public will find a multidisciplinary approach to issues of democratic values and governance encompassing research from Sociology, Digital Humanities, New Media, Psychology, Communication, International Relations and Economics.
English
Keywords: Sociology; Data, Algorithms, Democracy, Technology, Social Movements, Social Media, Protest